La aplicación Wordwall como herramienta didáctica para mejorar el proceso de aprendizaje en la asignatura de Matemática en los estudiantes de 5to año de Educación General Básica en la Escuela “Ángel Polibio Chaves” cantón Guaranda, provincia Bolívar en el periodo 2024. - Achupatin Toaza, María Elena (2025)
The research titled "The Wordwall application as a teaching tool to improve the learning process in the subject of Mathematics in 5th year students of Basic General Education at the “Ángel Polibio Chaves” school, Guaranda canton, Bolívar province in the period 2024", its main objective is to evaluate how the implementation of the Wordwall platform can contribute to improving the learning of Mathematics in students. The methodology used was a mixed approach, combining quantitative and qualitative techniques, surveys were carried out with the students and interviews with the Mathematics teacher, which allowed obtaining a comprehensive vision of the current use of technological tools in the classroom. The results revealed that most students were not familiar with Wordwall and that the teacher mainly used traditional resources, which limited innovation in teaching. Based on the findings, a methodological guide was designed that includes interactive activities in Wordwall, in order to strengthen the learning of Mathematics. In conclusion, the research highlights the potential of Wordwall as an effective educational tool that can enrich the learning experience in Mathematics, promote active participation and collaboration among students.